Electromagnetic Production of Hypernuclei - Terry Mart (Jurnal Matematika & Sains, 2007)
We review the progress in current understanding of the hypernuclear production through electromagnetic interaction. The motivation behind the interest in this investigation, i.e., the hyperon-nucleon force, is briefly overviewed. Special attention is given for the kaon productions on a deuteron and 3He. We also discuss some advantages of electromagnetic production of hypernucleus compared with the hadronic one.